2014
DOI: 10.1080/13549839.2014.967758
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive capacity and climate change: the role of community opinion leaders

Abstract: The contribution of the informal community sector to the development of collective response strategies to socioecological change is not well researched. In this article, we examine the role of community opinion leaders in developing and mobilising stocks of adaptive capacity. In so doing, we reveal a largely unexplored mechanism for building on latent social capital and associated networks that have the potential to transcend local-scale efforts -an enduring question in climate change adaptation and other cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 68 publications
0
13
0
1
Order By: Relevance
“…The previous study has shown that community leaders had an influential ability to succeed in the CBA project. According to [35], community leaders know about social, communication, and personal networks. To simplify, community leaders become a bridge for community members and formal institutions (government, NGO).…”
Section: Community Leadershipmentioning
confidence: 99%
“…The previous study has shown that community leaders had an influential ability to succeed in the CBA project. According to [35], community leaders know about social, communication, and personal networks. To simplify, community leaders become a bridge for community members and formal institutions (government, NGO).…”
Section: Community Leadershipmentioning
confidence: 99%
“…This warming climate condition happens due to the accumulation of greenhouse gases (GHG) in the atmosphere. landslides, drought, crop failure, biodiversity loss, sea level rise and human health [3].…”
Section: Introductionmentioning
confidence: 99%
“…Third Party Support by AHM Tbk[3].ISTEcS 20194. DiscussionTo deliver the results of the survey and verification of CVP location, on August 2016, a meeting was held in Jakarta on BPLHD People Participation division by inviting KPLH (board of environmental evaluators) Jakarta and representatives from CVP proposed region.…”
mentioning
confidence: 99%
“…More recently, integrated approaches to assessing various capitals simultaneously have emerged in relation to climate and global change in the Anthropocene (see for example Keys et al, 2016;Nelson et al, 2010;Smith et al, 2013), which is the point of departure for this paper in relation to the exploration of how capitals are expressed in the shift to new water management approaches and instances of urban flooding. As an example of this approach, the types of capitals more strongly expressed in the old' command and control water management approach may be: built and financial capital, as the old management approach is typified by centralized institutions and engineering solutions, while social capital may be expressed more strongly in the 'new' water management approach, as it is defined, in part, by adaptive capacity and learning (Schoeman et al, 2014).…”
Section: Theory Development: Conceptual Lensmentioning
confidence: 99%